Recent Updates on Indole Derivatives as Kinase Inhibitors in the Treatment of Cancer - Asati, Vivek; Bhupal, Ritu; Bhattacharya, Sushanta; Kaur, Kamalpreet; Gupta, GD; Pathak, Abhishek; Mahapatra, Debarshi K. (Anti-Cancer Agents in Medicinal Chemistry, 2023)
Cancer is becoming a global threat as its treatment accounts for many challenges. Hence, newer inventions prioritize the requirement of developing novel anticancer agents. In this context, kinases have been exclusively investigated and developed as a promising and novel class of drug targets for anticancer regimen. Indole derivatives have been found to be most effective for targeting multiple kinases, such as PIM, CDK, TK, AKT, SRC, PI3K, PKD, GSK, etc., to inhibit cell proliferation for cancer. Recently, a group of researchers have proposed their research outcomes related to this moiety, such as Zhang et al. described some potent PI3K inhibitors by substitution at the 4th position of the indole ring. Kassis et al. enumerated several potent CDK5 inhibitors by substituting the 2nd and 6th positions of the indole ring. In the present review, we have taken the initiative to summarize structure-activity relationship (SAR) studies of indole derivatives as kinase inhibitors for the development of potential inhibitors.
Keywords: clinical trial